Utility of Biogenic Iron and Its Bimetallic Nanocomposites for Biomedical Applications: A Review - Abedini, Ali; Rostami, Mojtaba; Banafshe, Hamid Reza; Rahimi-Nasrabadi, Mehdi; SobhaniNasab, Ali; Ganjali, Mohammad Reza (Frontiers in Chemistry, 2022)
Nanotechnology mainly deals with the production and application of compounds with dimensions in nanoscale. Given their dimensions, these materials have considerable surface/volume ratios, and hence, specific characteristics. Nowadays, environmentally friendly procedures are being proposed for fabrication of Fe nanoparticles because a large amount of poisonous chemicals and unfavorable conditions are needed to prepare them. This work includes an inclusive overview on the economical and green procedures for the preparation of such nanoparticles (flower, fruits, tea, carbohydrates, and leaves). Pure and bimetallic iron nanoparticles, for instance, offer a high bandwidth and excitation binding energy and are applicable in different areas ranging from antibacterial, anticancer, and bioimaging agents to drug delivery systems. Preparation of nano-sized particles, such as those of Fe, requires the application of high quantities of toxic materials and harsh conditions, and naturally, there is a tendency to develop more facile and even green pathways (Sultana, Journal of Materials Science & Technology, 2013, 29, 795–800; Bushra et al., Journal of hazardous materials, 2014, 264, 481–489; Khan et al., Ind. Eng. Chem. Res., 2015, 54, 76–82). This article tends to provide an overview on the reports describing green and biological methods for the synthesis of Fe nanoparticles. The present review mainly highlights selenium nanoparticles in the biomedical domain. Specifically, this review will present detailed information on drug delivery, bioimaging, antibacterial, and anticancer activity. It will also focus on procedures for their green synthesis methods and properties that make them potential candidates for various biomedical applications. Finally, we provide a detailed future outlook.